2020
DOI: 10.18061/1811/92031
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rurality on women's 'space for action' in domestic violence: Findings from a meta-synthesis

Abstract: Men's violence against women is a global human rights issue, with domestic violence one of the most common forms (World Health Organization, 2017). The consequences of domestic violence include detrimental effects on victim-survivors' health, well-being, and sense of safety. To understand these impacts, the concept of 'space for action' seeks to evaluate how perpetrators of domestic violence narrow women's life choices, constraining their freedom (Kelly, 2003). In this article, we build upon the concept of 'sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…We recognized that, compared to urban victim/survivors, those in nonurban locations face exacerbated barriers when seeking assistance (DeKeseredy & Schwartz, 2009;George & Harris, 2014;Hogg & Carrington, 2006). Abusers often capitalize on and seek to extend geographic and social isolation, including through technology (Farhall, Harris, & Woodlock, 2020). Risk in rural locations can be elevated by the sheer distance between a victim/survivor's residence and first responders.…”
Section: Background To Our Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We recognized that, compared to urban victim/survivors, those in nonurban locations face exacerbated barriers when seeking assistance (DeKeseredy & Schwartz, 2009;George & Harris, 2014;Hogg & Carrington, 2006). Abusers often capitalize on and seek to extend geographic and social isolation, including through technology (Farhall, Harris, & Woodlock, 2020). Risk in rural locations can be elevated by the sheer distance between a victim/survivor's residence and first responders.…”
Section: Background To Our Studymentioning
confidence: 99%
“…In essence, rurality brought forward barriers into our participants' lives. A wealth of literature has documented how geographic, social, and ideological structures and features in rural places can foster and facilitate violence (Farhall et al, 2020; see also Bosch & Bergen, 2006;Loxton, Hussain, & Schofield, 2003). In our study, as with our previous studies (see George & Harris, 2014;Harris, 2016), victim/ survivors described their communities as conservative or conducive to violence, because of localized gender roles and patriarchal values.…”
Section: Rurality and Patriarchal Gender Rolesmentioning
confidence: 99%
“…The connection between 'place', 'space' and 'spacelessness' has been largely overlooked in studies of digital abuse (DeKeseredy 2021a(DeKeseredy , 2021b. This is a significant oversight because, in non-urban zones, spacelessness, place and space restrict women's help-seeking and ability to exit relationships (their 'space for action') (Farhall, Harris and Woodlock 2020;Kelly 2003; Sharps-Jeffs, Kelly and Klein 2018) and may elevate the risk of fatal violence, as we discuss in this article. In the interests of protecting and empowering victim/survivors and regulating and preventing domestic violence, justice regulations of digital harms in different locations warrant attention.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we explore regional, rural and remote women's accounts of technology-facilitated abuse, which we term 'digital coercive control' (DCC), and invocation of police agencies in efforts to address these harms. We begin by outlining conceptual and theoretical frameworks used to understand DCC as 'spaceless violence': the behaviours to which our participants were subjected and how DCC, as well as geographic and social features of non-urban areas, may limit their 'space for action' (see also Farhall, Harris and Woodlock 2020). We then provide an overview of our project and the methodology adopted for conducting interviews and focus groups with female victim/survivors in three Australian states (New South Wales [NSW], Queensland and Victoria).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of these responses illustrates the patriarchal social structure of power in these regions, which is perpetuated in the interpersonal, institutional, and representational dimensions and keeps women in precarious, subordinate social positions, while ostracizing or punishing women who try to resist. Keywords violence against women, childhood sexual abuse, intimate partner violence, homelessness, rural areas, feminist studies More and more studies have shown that in non-urban areas, gender socialization centered on traditional roles and conservative values is especially persistent, complicating the life courses of women who experience intimate partner violence (DeKeseredy et al, 2016;Farhall et al, 2020;Savard & Marchand, 2016). In Canada, few studies have been done on violence against women in non-urban areas, but the information that has been gathered on this subject is alarming.…”
mentioning
confidence: 99%